Strobilanthes bolavenensis, a new species of Acanthaceae from Bolaven Plateau, southern Laos - Yamazaki, Kaito; Souladeth, Phetlasy; Tagane, Shuichiro (Phytotaxa, 2021)
A new species of Strobilanthes (Acanthaceae), S. bolavenensis, is described from Bolaven Plateau, southern Laos. Photos and illustration are given together with information of habitat, ecology, vernacular name and preliminary conservation assessment based on IUCN criteria.